Speciation of dissolved inorganic iodine in a coastal fjord: a time-series study from Bedford Basin, Nova Scotia, Canada - Shi, Qiang; Kim, Jong Sung; Wallace, Douglas W. (Frontiers in Marine Science, 2023)
We report a long-term (4.5 year) time-series with weekly resolution of iodide and iodate measurements made at 4 depths within the Bedford Basin: a 70 m deep, seasonally stratified, coastal fjord located near Halifax, Nova Scotia, Canada. The subsurface data (60 m) reveal strong inverse correlations of both iodide and total dissolved iodine (TDI) with dissolved oxygen and indicate that there is in-situ reduction of iodate in subsurface waters (in the presence of oxygen) as well as an additional external source of iodide from the remineralization of sinking organic matter, a flux from sediments, or both. Surface water (<10 m) iodide concentrations increase gradually from spring (70 nmol L-1) through fall (120-150 nmol L-1) and are not well represented by the current empirical parameterizations used to predict surface water iodide levels globally. The vertical gradient of iodide between subsurface and surface waters increases over the summer as a result of subsurface processes and, together with diapycnal mixing, may contribute to the seasonal accumulation of iodide in surface water. Examination of a global surface water iodide data compilation reveals an inverse relationship with subsurface oxygen concentrations which suggests that subsurface remineralization and sediment-water fluxes coupled with vertical mixing may also contribute to surface water iodide variability on a global scale.